A Critical Evaluation of Web Service Modeling Ontology and Web Service Modeling Language - Sharifi, Omid; Bayram, Zeki (Springer International Publishing Ag, 2016)
Web Service Modeling Language (WSML), based on the Web Service Modeling Ontology (WSMO), is a large and highly complex language designed for the specification of semantic web services. It has different variants based on logical formalisms, such as Description Logics, First-Order Logic and Logic Programming. We perform an in-depth study of both WSMO and WSML, critically evaluating them by identifying their strong points and areas in which improvement would be beneficial. Our studies show that in spite of all the features WSMO and WSML support, their sheer size and complexity are major weaknesses, and there are other areas in which important deficiencies exist as well. We point out those discovered deficiencies, and propose remedies for them, laying the foundation for a more tractable and useful formalism for specifying semantic web services.
31st International Symposium on Computer and Information Sciences (ISCIS) -- OCT 27-28, 2016 -- Krakow, POLAND
Keywords: Semantic web services; WSMO; WSML; Evaluation